Contrasting trajectories of morphological diversification on continents and islands in the Afrotropical whiteeye radiation - Day,JJ; Martins,FC; Tobias,JA; Murrell,DJ (Journal of Biogeography, 2020)
AimMorphological and lineage evolution are predicted to follow different patterns in island and mainland radiations. However, the extent to which these geographical contexts influence evolutionary trajectories remains poorly understood, in part because few studies have focused on speciesrich clades colonizing continents and archipelagos over comparable timeframes. Focusing on a diverse songbird clade radiating on the African continent and adjacent islands, we tested whether morphological evolution is best explained by adaptive or nonadaptive processes, and whether mainland and island lineages evolved to occupy different regions or volumes of morphological space (morphospace).LocationPalaeotropics, with a particular focus on the Afrotropical region.TaxonWhiteeyes, Zosterops (Aves: Zosteropidae).MethodsWe generated principal component axes from novel trait data for 120 species and combined this information with a comprehensive dated phylogeny. We then analysed the dynamics of trait and lineage diversification using comparative evolutionary methods.ResultsAn early burst and slowdown pattern of lineage accumulation is not mirrored by phenotypic evolution, which instead shows an apparent convergence on particular phenotypes. However, the overall signature of phenotypic convergence is strongly driven by mainland taxa, in which phenotypes appear to be highly constrained within elevational zones, while speciation events are often associated with phenotypic divergence from one body plan to the other after colonization of highland from lowland habitats, or vice versa. By contrast, island lineages have repeatedly explored novel areas of morphospace with patterns of phenotypic divergence generally not distinguishable from a randomwalk model.Main conclusionsDiversification of Zosterops highlights contrasting evolutionary trends and dynamics for continental versus island species. We suggest the different trajectory of evolution in insular lineages arises from reduced species